Assimilating e-learning barriers using an interpretive structural modelling (ISM) - Naveed, Quadri Noorulhasan; N. Qureshi, Mohamed Rafik; Alsayed, Alhuseen O.; Ahmad, Naim; Sanober, Sumaya; Shah, Asadullah (IEEE, 2017)
Nowadays, E-learning becomes a preferable medium for learning. Digital technology has made it more attractive and useful with additional user-friendly features. Basically, E-learning invloves massive infrastructure resources to operate. It also includes the effective combination of hardware and software along with the involvement of individuals to make the system successful for the students. Since the studnets and teachers have become agile using state-of-the-art communication technology in teaching learning process, they look for the efficient and smooth knowledge transfer. Many researchers have encountered the barriers for the successful implementations of E-Learning in the universities. There is little research that uncovers the interaction of E-Learning in the universities. There is little research that uncovers the interaction of E-Learning barriers. The present study aims to provide the interpretive structure modelling (ISM) and matrices d'impacts Croise's Multiplication Applique'e a' un Classement (MICMAC) based analysis to study such barriers of E-learning. A digraph representation ISM model has been established to help the stakeholders to understand the barriers to successful implementations of E-learning implementations of E-learning.